2018
DOI: 10.1016/j.bbrc.2018.03.146
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a non-phosphotransferase system for cis,cis-muconic acid production in Corynebacterium glutamicum

Abstract: Cis,cis-muconic acid (CCM) is a biochemical material that can be used for the production of various plastics and polymers and is particularly gaining attention as an adipic acid precursor for the synthesis of nylon-6,6. In the current study, the production of CCM was first attempted by introducing a newly developed protocatechuate (PCA) decarboxylase from Corynebacterium glutamicum 13032 to inha103, which completed the biosynthetic pathway therein. To improve CCM productivity, a phosphoenol pyruvate (PEP)-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…It has been shown that 3,4-DHBA displays antibacterial [ 3 ], antimutagenic [ 4 ], anti-inflammatory [ 5 ], antihyperglycemic [ 6 ] and highly antioxidant [ 7 ] effects. It also has potential applications for further microbiological synthesis of numerous valuable compounds, including the bioplastic precursor cis , cis -muconic acid [ 8 , 9 ]. To produce 3,4-DHBA from glucose, the synthesis of this compound from DHS, an intermediate in the common aromatic pathway, was previously implemented in E .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that 3,4-DHBA displays antibacterial [ 3 ], antimutagenic [ 4 ], anti-inflammatory [ 5 ], antihyperglycemic [ 6 ] and highly antioxidant [ 7 ] effects. It also has potential applications for further microbiological synthesis of numerous valuable compounds, including the bioplastic precursor cis , cis -muconic acid [ 8 , 9 ]. To produce 3,4-DHBA from glucose, the synthesis of this compound from DHS, an intermediate in the common aromatic pathway, was previously implemented in E .…”
Section: Introductionmentioning
confidence: 99%
“…Different microorganisms, such as Pseudomonas putida KT2440 [ 4 ], Amycolatopsis species ATCC 39116 [ 15 ], and E. coli [ 5 ] have been engineered to produce MA either via biosynthesis from glucose [ 6 8 ] and glycerol [ 2 ] or via biotransformation from aromatics [ 9 – 11 ]. The latter is particularly advantageous, because it requires only a few biochemical reactions and offers molar yields up to 100% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to aromatics-based biotransformation, de-novo biosynthesis of MA from glucose to glycerol is less efficient. So far, MA titer (5 g L −1 ) and productivity (0.03 g L −1 h −1 ) have remained rather low [ 2 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of engineering strategies to increase intracellular levels of PEP (phosphoenolpyruvate) and E4P (erythrose 4-phosphate), key intermediates of the shikimate pathway, and additional engineering to efficiently utilize various carbon sources including glucose, will lead us to obtain more efficient MA-producing Corynebacterium cell factories. Recently further engineered strain with deletion of the iolR gene which greatly increased glucose uptake has been developed, which had non-phosphotransferase system with increased PEP availability, showing improved MA production yield in the flask culture 55 .…”
Section: Discussionmentioning
confidence: 99%